Synesthesia in the Holy Quran: Functions and Aesthetics - Hamid Abbaszadeh; Mohammad Khaqani Isfahani (دراسات فی اللغه العربیه و آدابها, 2015)
Since the first studies in the field of the Quranic discourse, the artistic imagery has attracted the attention of the researchers. As more progress was made in research about the language and discourse of the Quran, the beauty and brilliance of the Quran increasingly fascinated the researchers. The audience were drowned in the intoxication of one source of beauty when another source of beauty was discovered to intoxicate the more. Synesthesia is an effective technique in imagery in which a desired effect is engendered with the involvement of more than one sense. This article uses descriptive-analytical method to explore synesthesia in 260 Quranic verses, which include action verbs, after defining them and reviewing their use in previous texts. This research elaborates on the role of the five senses on cognition and the creation of knowledge. It intends to shed light on the aesthetics of the Holy Qur'an. The Quran has use synesthesia to the full effect as there is complete coordination among the senses involved in the images produced. For example, it has mixed tactile sense and the sense of taste to show the extent of the sufferings. Synesthetic images enjoy positive sides which include novelty, wit, polysemy, and depth of impact.